Stress and the brain: Perceived stress mediates the impact of the superior frontal gyrus spontaneous activity on depressive symptoms in late adolescence - Wang, Song (Hum Brain Mapp, 2019)
Identifying factors for the prediction of depression is a long‐standing research topic in psychiatry and psychology. Perceived stress, which reflects the tendency to appraise one's life situations as stressful and overwhelming, has emerged as a stable predictor for depressive symptoms. However, the neurobiological bases of perceived stress and how perceived stress influences depressive symptoms in the healthy brain remain largely unknown. Here, we investigated these issues in 217 healthy adolescents by estimating the fractional amplitude of low‐frequency fluctuations (fALFFs) via resting‐state functional magnetic resonance imaging. A whole‐brain correlation analysis showed that higher levels of perceived stress were associated with greater fALFF in the left superior frontal gyrus (SFG), which is a core brain region for cognitive control and emotion regulation‐related processes. Mediation analysis further indicated that perceived stress mediated the link between the fALFF in the left SFG and depressive symptoms. Importantly, our results remained significant even when excluding the influences of head motion, anxiety, SFG gray matter structure, and school environment. Altogether, our findings suggested that the fALFF in the left SFG is a neurofunctional marker of perceived stress in adolescents and revealed a potential indirect effect of perceived stress on the association between the SFG spontaneous activity and depressive symptoms.